2019
DOI: 10.29252/jafm.12.06.29876
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Natural and Ventilated Cavitation around a Base Ventilated Hydrofoil

Abstract: In more recent years, supercavitation has attracted intensive attention due to its potentials in drag reduction for underwater vehicles. Ventilation is acknowledged as an efficient way to enhance cavitation when vehicles work under low speed. That means natural and ventilated cavitation may coexist in the flow and the interaction between the natural cavitation and ventilated cavitation has to be considered. In this paper, ventilated cavitating flow with natural cavitation around a base-ventilated hydrofoil is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 18 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Reducing vessel resistance by using ventilated cavities has been a highly researched topic in the marine industry [1][2][3][4]. Numerous studies on ventilated cavities have demonstrated that injecting non-condensable gas around the submarine surface can create a cavity at low speeds and high environmental pressures, thereby effectively reducing the frictional resistance of the submarine [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Reducing vessel resistance by using ventilated cavities has been a highly researched topic in the marine industry [1][2][3][4]. Numerous studies on ventilated cavities have demonstrated that injecting non-condensable gas around the submarine surface can create a cavity at low speeds and high environmental pressures, thereby effectively reducing the frictional resistance of the submarine [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%